Principles and algorithms of psychotherapy of maladaptive states for students - Khaustov, Maksim (Journal of Education, Health and Sport, 2017)
142 students of Kharkov National Medical University (KNMU), both genders, aged 18.0 ± 2.0 years old were examined. 52.2% of the persons under examination were inhabitants of the Eastern Ukraine, 21.1% - those from Luhansk and Donetsk regions entering KNMU before the anti-terror operation began and 26.7 % - forcibly displaced persons from ATO zone. We have developed and tested the system of psychotherapeutic correction of states of maladaptation in the students of the medical university, which consists of four consecutive stages: I - the stage of forming a compliance, the primary adaptation to the psychotherapeutic process. II - the psycho-educational stage aimed at leveling the students’ knowledge deficit about the mechanisms of formation and the peculiarities of the course of adaptation disorders. III - the correctional stage aimed at stabilizing the emotional state, forming an adaptive form of behavior. IV - consolidate and support the results by potentiating positive emotions, prevention of relapse of maladaptive states. As the results of dynamic observation on the background of the proposed system of psychotherapeutic correction of maladaptation showed, the level of adaptation of students was significantly increased, anxiety depressive symptoms were reduced, the level of neuro-psychic stress was declined.